Marine Growth Rate Prediction of Wellhead Offshore Platform - Kadhafi, Muammar; Herucakra, Wira; Abdullah, Sholeh Khuddin; Putra, Wahyu Suryo (Institut Teknologi Adhi Tama Surabaya, 2024)
Marine growth, though a straightforward issue, which is can lead the significant problems for marine structures such as wellhead jacket platforms. The survey was conducted to measure the thickness of marine growth from the splash zone downward to the seabed elevation of the jacket platform. The growth rate was calculated and predicted for 10 years from initial conditions, while the initial conditions were set 3 years after the operation started. The result indicated that the prediction thickness exceeded the allowable thickness at 5 years start from the initial condition. The results of these measurements and predictions can be used for management policy-making and followed up with an assessment of the effects of marine growth on structural performance such as seismic and structural fatigue analysis.